APLIKASI KASCING DAN N, P, K TERHADAP TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt) - Admiral, Ade; ', Wardati; ', Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
One of the efforts to produce the sweet corn of high production and good quality,certainly should pay attention to nutrient availability in the soil. It is considering the plant sweet corn is in need of adequate nutrient supply. One way to increase production of sweet corn plant withfertilizing, fertilizingwith right doses, right way and the right timeincreasesproduction of sweet corn plants. The objective of the research wasto get the bestinteraction of giving vermicompost and N, P, K on growth and production of sweet corn plants. This research arranged experimentaly using Randomized Block Design(RBD) which consists of 9 individual interactions 3 repeats, so the retrieved 27 units where each unit of experimental trials there are 24 plants and 5 plants used as samples. Parameters observed were the plant height, stament appear time,cob diameter withoutcornhusk,coblengthwithoutcornhusk, cob weight withoutcornhuskpersample and productionperplotwithoutcornhusk. The results show that the interaction of vermicompost and N, P, K on 4,5 ton/ha dose of vermicompost and N, P and K (300 kg/ha of Urea SP-36 200kg/100 kg KCL/ha ha) gaves the best effect on the growth and production of sweet corn. Keywords: sweet corn, vermicompost, N,P,K fertilizer